The Art of Others: The Birth of the Aesthetic Discourse on Japanese Art in France at the Turn of the Twentieth Century - Malachi, Miriam (Mabatim: Journal of Visual Culture, 2022)
The art historian Henri Focillon (1881–1943) was among the first scholars in the French academy to specialize in Japanese art at the beginning of the twentieth century. Between 1912 and 1921, Focillon published books and articles, taught a course on Japanese art at the University of Lyon, and initiated as well as participated in an international conference on Japanese art held in France. He belonged to a small group of historians in the French academy who were active in the late phase of the great commercial vogue for Japanese art and artifacts in Europe and the United States – an aesthetic movement known in French as Japonisme (1870–1910s). Japonisme played a decisive role in advancing the study of Japanese art within a Western model of art history, largely thanks to its emphasis on the availability of Japanese artworks and artifacts in France. The new presence of Japanese art in France offered a promising and exciting field for a young historian. Yet the research conditions of the time did not support a scholar of Focillon’s stature, and in the early 1920s he abandoned the field entirely, turning instead to the historical study of French Gothic art. His departure underscored the difficulties faced by Western historians and the problems that arose within the discipline of Western art history when confronting a “foreign” art. What were the conflicts that Focillon encountered as a historian of Japanese art in France? Who were the principal cultural agents in the Orientalist sphere of fin-de-siècle France who carried the study of Japanese art up until the decline of Japonisme? This article surveys the most important books on Japanese art published in France from 1870 to the early 1920s, before Focillon. It first examines the discourse on Japanese art in late nineteenth-century France: Who were the central cultural agents operating in this arena? What forces drove the publications on Japanese art? Who were the earliest historians engaged in this work? And what were the boundaries of discourse on art in general, and on Japanese art in particular, during this period? As a conceptual framework, the article engages with questions of identity and otherness through the lens of cultural critique, in order to understand the beginnings of Western perceptions of Japanese art, the differences between this perception in the West and the reception and status of art in Japan, and why such disparities emerged between the two.